Factors Influencing Land Mafia Cases - Aarce Tehupeiory (International Journal of Artificial Intelligence Research, 2022)
The technique of collecting data in this study is through interviews in a checklist sheet and using other methods that are in accordance with the research approach. By not taking sides, transparency, accountability, and the principle of respect for those who have good ethics towards land with the spirit of creating justice in the land sector for people who seek justice. Suggestions Need to strengthen optimizing the role of the Land Mafia Task Force in preventing and eradicating Land Mafia practices, namely that a commission for eradicating land mafia can be formed, at least an anti-land mafia commission is created, even if necessary, a separate judiciary is formed in terms of resolving land disputes and land conflicts and its existence is strengthened by involving academics who correctly understand the problems and principles of land use control.